Pengaruh Emotional Intelligence Terhadap Subjective Career Success Melalui Career Adaptability Dan Career Resilience - Siska Sindi Fitriana; Andre Dwijanto Witjaksono; Anang Kistyanto (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the effect of emotional intelligence on subjective career success by examining the mediating role of career adaptability and career resilience. This research employs a quantitative approach with an explanatory research design. The population consists of alumni of the Master of Management Program at Universitas Negeri Surabaya, with a sample of 64 respondents selected using purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results indicate that emotional intelligence does not have a direct effect on subjective career success. However, emotional intelligence has a positive and significant effect on career adaptability and career resilience. Furthermore, career adaptability and career resilience significantly influence subjective career success and mediate the relationship between emotional intelligence and subjective career success. These findings suggest that subjective career success is not solely determined by emotional intelligence but also by an individual’s ability to adapt and remain resilient in a dynamic work environment.